Advanced Materials in Catalysis and Adsorption (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The recent studies focused on development of advanced carbon nanostructured materials, functionalized carbons, nanostructured oxides, electrocatalysts, and catalytic composite materials are collected in this reprint. The advantage of using novel catalytic materials and adsorbents in various applications is demonstrated.